Progressive Legal Paradigm in Batam's Fiscal Transformation: Regulatory Reconstruction Towards Eco-Digital Logistic Hub 2045 - Totok Catur Wismo Malaicanto (Universitas Islam Sultan Agung, 2026)
The development of the digital economy has driven significant growth in e-commerce activities, including in free trade zones. This situation creates new challenges in the implementation of Value Added Tax (VAT) policies, particularly related to tax administration mechanisms, digital transaction oversight, and the balance between state revenue interests and the sustainability of digital economy actors. This study aims to analyze VAT policies on e-commerce in free trade zones and formulate a policy reconstruction model that is fairer and more adaptive to the development of the digital economy. This study uses a normative legal research method with a legislative approach, a conceptual approach, and a comparative approach. The theoretical framework of this study uses the theory of distributive justice proposed by John Rawls. The results show that VAT policies on e-commerce still face various problems, including the complexity of tax administration, limited oversight of digital transactions, and high compliance costs for micro and small businesses. Therefore, this study proposes a reconstruction of digital VAT policies through the implementation of a Simplified VAT Scheme, a Marketplace Tax Collection Model, and special regulations for small-value digital transactions. This policy model is expected to create a digital tax system that is simpler, fairer, and able to support the development of the digital economy in free trade zones.